Pendampingan Berbasis Alat Permainan Edukatif sebagai Strategi Pemulihan Psikososial Anak Sekolah Dasar Pascabanjir di Desa Bungkaih Aceh Utara - Mutia Fonna; Iryana Muhammad; Siraj Siraj; Muhammad Yusuf; Teuku Azhari; Muliana Muliana; Nur Elisyah (Lembaga Pengembangan Kinerja Dosen, 2026)
Floods are hydrometeorological disasters that not only cause physical damage but also significantly affect children’s psychosocial well-being. This community engagement program aimed to strengthen children’s psychosocial conditions after flooding through a community-based mentoring approach focused on emotional and social recovery. The program was conducted in Bungkaih Village, Muara Batu Subdistrict, North Aceh Regency, by lecturers and students of the Faculty of Teacher Training and Education, Universitas Malikussaleh, as part of the Teaching Volunteer Program. The approach employed was Participatory Action Research (PAR), involving 160 children as the primary participants throughout the implementation process. The mentoring activities included educational games for trauma healing, play-based learning activities, creative expressions, and group interactions designed to support children’s social and emotional development. The results indicated improvements in children’s sense of safety, self-confidence, and participation in learning and social activities, accompanied by reduced anxiety following the disaster. These findings highlight that community-based psychosocial mentoring is an effective strategy for accelerating children’s recovery and strengthening community resilience in responding to disaster impacts.